Tenofovir alafenamide in the treatment of chronic hepatitis B virus infection: rationale and clinical trial evidence - Byrne, Ruth (Therap Adv Gastroenterol, 2018)
Tenofovir alafenamide (TAF), a novel prodrug of tenofovir was developed to deliver enhanced antiviral potency and reduced systemic toxicities by more efficient intracellular delivery of the active metabolite tenofovir disphosphate than tenofovir disoproxil fumarate (TDF). In two randomized, double-blind, multinational phase III trials in patients with hepatitis B e antigen (HBeAg)-positive or -negative infection, TAF 25 mg was non-inferior to TDF 300 mg in achieving the primary efficacy outcome of a hepatitis B virus (HBV) DNA level < 29 IU/ml at week 48 and was associated with higher rates of alanine aminotransferase (ALT) normalization based on AASLD (American Association for the Study of Liver Diseases) criteria. TAF was well tolerated with low rates of adverse events, comparable to TDF. A significantly lower decline in the estimated glomerular filtration rate (eGFR) was observed in patients receiving TAF compared with patients receiving TDF and loss of bone mineral density at the hip and spine was significantly lower in the TAF groups. These trends continued to week 96. The requirement for long-term therapy in chronic HBV highlights the importance of these efficacy and safety trends, however their true clinical relevance is yet to be established and further studies with long-term follow up and real-world clinical data are needed.